Factors affecting the quality of life after total knee arthroplasties: a prospective study - Papakostidou, Ippolyti (BioMed Central, 2012)
BACKGROUND: The purpose of the study is to evaluate the self-reported outcomes in the first year after primary total knee arthroplasty (TKA), and to determine factors influencing the quality of life (QoL) 6 weeks, 3, 6, and 12 months after TKA. METHODS: A cohort of patients with knee osteoarthritis undergoing primary TKA at two hospitals (a regional university hospital and a capital’s metropolitan hospital) was prospectively followed for 12 months. Patients were assessed preoperatively and at 4 postoperative time-points, with the use of self-reported measurements for pain, physical function and depression with the following evaluation tools: Western Ontario and McMaster Osteoarthritis Index [WOMAC], Knee Society Scoring system [KSS], Centre for Epidemiological Studies Depression Scale, [CES-D10] and visual analog scale [VAS] for pain). General linear modelling for repeated measures was used to evaluate the effect of each independent variable including clinical and sociodemographic data. Differences between groups at different time points were tested by the independent samples t-test. RESULTS: Of the 224 eligible patients, 204 (162 females, mean age 69.2) were included in the analysis. Response rate at one year was 90%. At 6 weeks after surgery, despite improvement in pain and alleviation of the depressive mood, the physical function remained less satisfactory. Females presented lower scores in terms of quality of life, both preoperatively and 6 weeks after TKA. Significant improvement was already experienced at 3 months postoperatively. According to WOMAC, KSS, CES-D10 and pain VAS scores the Qol was significantly improved 12 months after TKA (P < 0.001). CES-D10 score was positively correlated with WOMAC and pain VAS scores at all the time points assessed (P < 0.001). Age, body mass index (BMI), place of residence, level of education and social support were not significant predictors of QoL after TKA. CONCLUSIONS: Patients experienced great improvement in their QoL after TKA in spite of a less satisfactory physical function in the first 6 weeks after surgery, with noticeable differences in the QoL among genders in the same time period. After that period all patients experienced significant improvement for all the measured parameters, until the third postoperative month with smaller changes thereafter.